Jeremy McInerny. Greece in the ancient world / Richard T. Neer. Art and archaeology of the Greek world. A new history, c.2500-c.150 BCE - Cartledge, Paul (Journal of Greek Archaeology, 2019)
Jeremy McInerny. Greece in the ancient world. pp. 368, 273 colour illustrations. 2018. London and New York: Thames and Hudson. ISBN 978–0–500–25226–0. £35 Richard T. Neer. Art and archaeology of the Greek world. A new history, c.2500-c.150 BCE. Second edition. pp. 408, 559 colour illustrations. 2019. London and New York: Thames and Hudson. ISBN 978–0–500–052082. £45